Fiscal Policy in Islamic Perspective Tracking from Historical Literature Review - Zikra Hayati; Istiqamah Mulya Ulfah; Suci Ananda; Muhammad Randha Siregar (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
The policy known as fiscal policy controls or manages state revenues and expenditures with the aim of maintaining stability and promoting economic growth. One of the tools of fiscal policy is government revenue and expenditure. Except for distribution theory, none of the literature on fiscal policy discusses ethical issues. Even in this case, it is still limited to distribution theory. Liberal studies are used in this research approach. The conclusion of this discussion shows that Islamic fiscal policy has always relied on a balanced budget system, or balanced budget, managed by the baitul mal since the time of the prophet SAW. The terms zakat, infaq, shadaqah, waqf, ghanimah, fa'i, kharaj, jizyah, u'shur, and khums are some of the tools used in Islamic fiscal policy. This research is organized using a type of research known as a literature review. A systematic literature review framework follows a top-down approach, where relevant scholarly journals or databases are searched thoroughly to identify synthesized documents.